Cardiac computed tomography - Current diagnostic role in cardiology - Achenbach, Stephan (Deutsche Medizinische Wochenschrift, 2022)
Computed tomography (CT) imaging of the heart requires specific equipment and protocols in order to synchronize image generation with the electrocardiogram (ECG), usually achieved via ECG-gated reconstruction or ECG-triggered acquisition. The main application of cardiac CT is coronary artery imaging. Contrast-enhanced coronary artery CT allows the identification and rule-out of stenoses and is a diagnostic approach to patients with suspected chronic coronary artery disease or acute chest pain, provided that patient characteristics are associated with a high likelihood of fully diagnostic image quality. In addition, CT has the potential to visualize coronary atherosclerotic plaque, even if non-obstructive, and data suggest that this may be a valuable guide towards more intensive risk modification strategy such as statin therapy. In recent years, the use of CT imaging to guide structural heart interventions has become another important application, and many interventions, such as transcatheter aortic valve implantation, substantially depend on CT imaging to plan the procedure, minimize risks, and optimize outcome.
CRIS-Team WoS Importer:2022-05-13